PENERAPAN METODE INQUIRY TERHADAP HASIL BELAJAR SISWA PADA MATA PELAJARAN IPS TERPADU DALAM MATERI KERAGAMAN FLORA DAN FAUNA DI INDONESIA DI KELAS VII SMP NEGERI 1 TEBAS - Suwarno, Agus (Refleksi Edukatika : Jurnal Ilmiah Kependidikan, 2016)
The problem in this research is "Implementation Methods of Inquiry Against Student Results AtSubjects IPS Integrated In Creative Diversity Flora And Fauna In Indonesia In Class VIIJunior High School 1 Tebas", with sub-problems of research: (1) student learning control classwho did not apply his method of inquiry in social studies Integrated in the material diversity offlora and fauna in Indonesia in class VII SMP Negeri 1 Tebas. (2) The results of theexperimental class students learn to apply methods of inquiry in social studies Integrated in thematerial diversity of flora and fauna in Indonesia in class VII SMP Negeri 1 Tebas. (3) Thedifference in student learning outcomes with the experimental class control class thatimplements the method of inquiry in social studies Integrated in the material diversity of floraand fauna in Indonesia in class VII SMP Negeri 1 Tebas. The variables in this study consistedof the dependent variable and independent variables, the independent variable of this researchis the result of learning and the independent variables are methods of inquiry. This study usedan experimental method, the research is a form of quasi-experimental research or experimentwith the study design quasy two-group post-test only design. The population in this study theentire seventh grade students totaling 196 people. The sampling technique using clustersampling. Data collection techniques used in this study is the direct observation techniques,measurement techniques, and documentary techniques. And tools used are observation sheets(IPKG 2), achievement test, and documentation. Based on the analysis and discussion of dataobtained: (1) the average student learning outcomes in control class is 69.62 which is quiteenough. (2) The results of the calculation, the average student learning outcomes in theexperimental class at 73.23 which is quite good. (3) based on calculations using the t test wasobtained tcount ≥ ttable, 2.27 ≥ 2.00 then there is a difference in student learning outcomes with theexperimental class control class that implements methods of inquiry.